Factors Affecting Organizational Performance: A Study on Four Factors: Motivation, Ability, Roles, and Organizational Support - Bunteng, Long (Srawung: Journal of Social Sciences and Humanities, 2022)
The purpose of this study is to identify the factors affecting the organizational performance. Four factors, motivation, ability, roles, and situation, will be in-dept identified to explore how each factor positively impacts the organizational performance. The study is conducted, using applied qualitative descriptive approach and analysis method. The fours factors (Motivation, Ability, Roles, Organizational Support) are adopted from a few previous studies. Each factor is studied and analyzed based on empirical papers that have been observed, tested, and experienced by vaiours articles from different countries’ authors. After the description of each factor, it is found that a number of organizations have been considerably affected by these four factors. In addition, each factor is found to be very dependent to one another. A constant growth of organizational performance should be steadily dependent on the four factors, meaning that the organization should apply all the four factors at the same time to ensure its constant increasing performance. It is noted that an absence of one factor will definitely lead to the fall and decrease of the performance of the organization and the presence of the four factors at the same time will definitely ensure the increasing performance of the organization.